Internalisasi Nilai-Nilai Pendidikan Agama Islam Melalui Program Infaq Di Smk Negeri 1 Lamongan - Wahyuni Ahadiyah; Jaziaturrasyidah (Akademika, 2024)
This research is entitled, Internalization of Islamic Religious Education Values Through the Infaq Program. This research is motivated by the importance of understanding the values of Islamic religious education through the infaq program. This is because there are still many students who are more concerned with themselves, lack caring values, empathy values and are less willing to set aside wealth to share. This research aims to describe the process of internalizing the values of Islamic religious education through the infaq program. This research uses a qualitative case study type of research. Data collection uses interview, observation and documentation methods. This research focuses more on 1) How is the infaq program implemented at SMK Negeri 1 Lamongan? 2) What is the process of internalizing the values of Islamic religious education through the infaq program at SMK Negeri 1 Lamongan? The results of this research are, 1) The infaq program at SMKN 1 Lamongan is implemented every day for teachers and every Friday for students. 2) The process of internalizing the values of Islamic religious education through the infaq program at SMKN 1 Lamongan by transferring knowledge and then the teacher providing examples so that students gradually follow. The values internalized by students are the values of worship and moral values. The methods used are the story method, uswatun hasanah method, habituation method, mau'idhoh hasanah method, and warning method